Autoestima de pessoas com úlcera venosa - Amanda Jéssica Gomes de Souza; Samilly Márjore Dantas Liberato Campos; Marina Góes Salvetti; Cintia Galvão Queiroz; Gilson de Vasconcelos Torres; Isabelle Katherinne Fernandes Costa (Universidade Federal do Ceará, 2017)
to verify the level of self-esteem of people with venous ulcer and its relationship with sociodemographic, care and clinical characteristics. Methods: cross-sectional study with 44 patients with venous ulcers assisted in primary health care and evaluated using the Rosenberg Self-Esteem Scale. Descriptive and inferential statistics were performed. The t-test was to compare means of the scale scores in relation to sociodemographic, care and clinical characteristics. Results: the mean self-esteem was 9.3 (± 5.1). The variables that showed association with self-esteem were: married/common-law married patients (p=0.016), with occupation (p=0.023), using compressive therapy (p=0.040), under less than six months of treatment (p=0.014), and with small ulcers (p=0.010). Conclusion: the self-esteem of patients with venous ulcers was satisfactory/high, and it was especially higher among those with partner, with occupational activity, making use of compressive therapy, at the initial phase of the treatment and who had small ulcers.